A Systematic Review of Reasons and Risks for Acute Service Use by Older Adult Residents of Long-term Care - Merrick, Eamon; Bloomfield, Katherine; Seplaki, Christopher; Shannon, Kay; Wham, Carol; Winnington, Rhona; Neville, Stephen; Bail, Kasia; Fry, Margaret; Turner, Murray; MacFarlane, Joanna (Wiley, 2024)
AIMS AND OBJECTIVES: To identify the reasons and/or risk factors for hospital admission and/or emergency department attendance for older (≥60 years) residents of long-term care facilities. BACKGROUND: Older adults' use of acute services is associated with significant financial and social costs. A global understanding of the reasons for the use of acute services may allow for early identification and intervention, avoid clinical deterioration, reduce the demand for health services and improve quality of life. DESIGN: Systematic review registered in PROSPERO (CRD42022326964) and reported following PRISMA guidelines. METHODS: The search strategy was developed in consultation with an academic librarian. The strategy used MeSH terms and relevant keywords. Articles published since 2017 in English were eligible for inclusion. CINAHL, MEDLINE, Scopus and Web of Science Core Collection were searched (11/08/22). Title, abstract, and full texts were screened against the inclusion/exclusion criteria; data extraction was performed two blinded reviewers. Quality of evidence was assessed using the NewCastle Ottawa Scale (NOS). RESULTS: Thirty-nine articles were eligible and included in this review; included research was assessed as high-quality with a low risk of bias. Hospital admission was reported as most likely to occur during the first year of residence in long-term care. Respiratory and cardiovascular diagnoses were frequently associated with acute services use. Frailty, hypotensive medications, falls and inadequate nutrition were associated with unplanned service use. CONCLUSIONS: Modifiable risks have been identified that may act as a trigger for assessment and be amenable to early intervention. Coordinated intervention may have significant individual, social and economic benefits. RELEVANCE TO CLINICAL PRACTICE: This review has identified several modifiable reasons for acute service use by older adults. Early and coordinated intervention may reduce the risk of hospital admission and/or emergency department. REPORTING METHOD: This systematic review was conducted and reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology. PATIENT OR PUBLIC CONTRIBUTION: No patient or public contribution.
Keywords: aged; emergency service; hospital; hospitalisation; long‐term care; aged; emergency service; hospital; hospitalisation; long‐term care; 4203 Health Services and Systems; 4205 Nursing; 42 Health Sciences; Prevention; Aging; Health Services; Clinical Research; 3.1 Primary prevention interventions to modify behaviours or promote wellbeing; Generic health relevance; 1110 Nursing; 1117 Public Health and Health Services; 1701 Psychology; Nursing; 4203 Health services and systems; 4205 Nursing; Humans; Long-Term Care; Aged; Aged, 80 and over; Hospitalization; Risk Factors; Female; Male; Emergency Service, Hospital; Middle Aged; Humans; Hospitalization; Long-Term Care; Risk Factors; Aged; Aged, 80 and over; Middle Aged; Emergency Service, Hospital; Female; Male; Humans; Long-Term Care; Aged; Aged, 80 and over; Hospitalization; Risk Factors; Female; Male; Emergency Service, Hospital; Middle Aged